Struggling with Tradition: Making Room for Same-Sex Weddings in a Liberal Jewish Context - Lash, Shari (Ethnologies)

(untitled) (Association Canadienne d'Ethnologie et de Folklore, 2006)
Despite growing acceptance of homosexuality in mainstream popular culture, debates about legalizing same-sex unions continue largely because they conflict with religious notions of heterosexual marriage and family. Marriage has become a symbol of status, making public weddings a sought-after goal for marginalized groups to gain greater social acceptance. Liberal Judaism particularly has responded to changing cultural circumstances and adapted tradition to meet the needs of diverse worshippers within a growing spiritual marketplace. These branches of the tradition contend with problematic textual and ritual elements that have obstructed the acceptance of gay, lesbian, bisexual, and queer Jews into their communities. Alternative understandings of Leviticus 18:22 and the Talmudic concept of kiddushin make room for same-sex weddings to occur in the synagogue. Because same-sex marriage challenges dominant attitudes about what constitutes a conventional family, wedding ceremonies performed in religious settings can transform communities that witness them, especially within Canada where same-sex marriage is legal.